Pengaruh Variasi Fraksi Volume Biokomposit,Serat Daun Nanas dan Resin Epoxy-Polyester Terhadap Kekuatan Bending dan Daya Serap Air - Diega, Muhammad Veros; Kencanawati, Cok Istri Putri Kusuma; Negara, Dewa Ngakan Ketut Putra (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract The development of the compositee industry in Indonesia requires alternative materials that are more environmentally friendly and oriented towards low prices, abundant quantities, high quality, and environmental friendliness. So far, the development of composites in Indonesia has been focused on non-renewable natural resources such as glass, carbon, and aramid. Therefore, it is necessary to develop environmentally friendly composite material reinforcement materials, such as natural fibers. Natural fiber composites are abundant in Indonesia, including bamboo fibers, sugarcane fibers, banana fibers, and others. Utilizing these fibers as composite reinforcement can become a better alternative for the composite industry in Indonesia. This study also uses a mixed epoxy-polyester resin with a ratio of 9:1 and a hardener of 2:1 as the matrix. The composition of fibers with resin uses a volume fraction of 5% fibers: 95% resin, 10% fibers: 90% resin, and 15% fibers: 85% resin. It is molded using an acrylic mold with a hand lay-up technique. The specimen size is based on ASTM D790-03 for bending tests and ASTM D570-98 for water absorption tests. Data from the bending test results show that the highest bending stress and modulus of elasticity values are obtained in the 15% variation of pineapple leaf fiber at 35.969 Mpa and 0.918 Mpa, while the highest strain value in the 10% variation is 9.409%. However, the 15% variation has the lowest strain value of 3.773%. In the water absorption test, the highest absorption was obtained in the 15% fiber fraction of 3,36 % and the lowest absorption in the 5% fiber fraction of 2,27%. With the results of the water absorption test above, the 15% fiber fraction became the highest absorption value. This happens because fiber affects the water absorption ability of the specimen. Keywords: Pineapple Leaf Fiber, Epoxy Resin, Polyester Resin, Epoxy Polyester Resin Blend, Volume Fraction, Bending Test, Water Absorbency Test